AIAA/AAS Astrodynamics Specialist Conference 2014
DOI: 10.2514/6.2014-4304
|View full text |Cite
|
Sign up to set email alerts
|

Applying Dynamical Systems Theory to Optimize Libration Point Orbit Stationkeeping Maneuvers for WIND

Abstract: NASA's WIND mission has been operating in a large amplitude Lissajous orbit in the vicinity of the interior libration point of the Sun-Earth/Moon system since 2004. Regular stationkeeping maneuvers are required to maintain the orbit due to the instability around the collinear libration points. Historically these stationkeeping maneuvers have been performed by applying an incremental change in velocity, or Δv, along the spacecraft-Sun vector as projected into the ecliptic plane. Previous studies have shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The relativistic form of this problem considering the radiation force was given by Robertson [22]. Several studies ( [2], [3], [5], [11], [12], [25]) of the restricted problem have since been analyzing the effect of radiation pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The relativistic form of this problem considering the radiation force was given by Robertson [22]. Several studies ( [2], [3], [5], [11], [12], [25]) of the restricted problem have since been analyzing the effect of radiation pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the target point method, Gómez et al [81] showed the advantages of the Floquet mode approach in terms of qualitative behaviour of the controller. Using the symmetries in the RTBP, a x-axis velocity constraint at the x − ẑ plane crossings (the plane orthogonal to the ecliptic that contains the primaries) strategy was used by NASA for some LPOs missions [82,83]. The idea behind this method is to determine the maneuvers that ensure that the velocity component along the x-axis is zero when crossing the x − ẑ plane (after one or two revolutions).…”
Section: Station Keeping Strategiesmentioning
confidence: 99%